Complaining and sharing personal concerns as political acts: how everyday talk about childcare and parenting on online forums increases public deliberation and civic engagement in China. Issue 2 (3rd April 2022) - Sun, Yu; Graham, Todd; Broersma, Marcel
ABSTRACT: Based on a comparative content analysis of political talk in three popular Chinese online forums (government-run, commercial-lifestyle, and commercial-topical), this paper investigates how the private and public spheres are connected thru everyday talk about childcare concerns. Compared to the government-run (party-state) forum, the nonpolitical (lifestyle and topical) forums created open and inclusive 'third spaces' for citizens to engage in child welfare politics. In such spaces, the reason, rule-based deliberation was not the dominant communicative practice. Rather, political (narrative) acts of complaining and sharing personal concerns – grounded in citizens' life experiences – were the norm, capturing and recognizing public problems in the private sphere. We argue that to understand the nature of political talk in Chinese third spaces, communicative acts that have not been considered central to deliberative reasoning, such as complaining and sharing personal concerns should be given more normative importance.